AIRCRAFT VENTILATION SYSTEMS OFTEN INADEQUATE TO REMOVE CIGARETTE SMOKE; PASSENGERS AND CREW COMPLAIN (Tufts Archival Research Center, 2007)
Press release from the American Association for Respiratory Care regarding aircraft ventilation systems. Explains that accurate research studies are difficult to perform aboard an aircraft but cites National Research Council (NRC) sources detailing passenger complaints due to smoky air. Lists reasons that improving ventilations systems in aircraft are economically unfeasible and therefore support the NRC recommendation to ban smoking aboard all aircraft.